2011
DOI: 10.1080/00140139.2011.604431
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cognitive workload on physiological arousal in young adult drivers: a field study and simulation validation

Abstract: Physiological measures provide a continuous and relatively non-invasive method of characterising workload. The extent to which such measures provide sensitivity beyond that provided by driving performance metrics is more open to question. Heart rate and skin conductance were monitored during actual highway driving in response to systematically increased levels of cognitive demand using an auditory delayed digit recall task. The protocol was consistent with an earlier simulator study, providing an opportunity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(88 citation statements)
references
References 32 publications
6
82
0
Order By: Relevance
“…Cinaz et al (2013) indicated that the LF/HF ratio significantly increases with increased MWL. Reimer and Mehler (2011) monitored HR during actual highway driving in response to systematically increased levels of MWL using an auditory delayed digit recall task. The pattern of change in HR with increased MWL was highly consistent between field and simulator conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cinaz et al (2013) indicated that the LF/HF ratio significantly increases with increased MWL. Reimer and Mehler (2011) monitored HR during actual highway driving in response to systematically increased levels of MWL using an auditory delayed digit recall task. The pattern of change in HR with increased MWL was highly consistent between field and simulator conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological parameters were also found to correlate to the cognitive workload in previous studies [7]- [9]. The method has been used priviously to assess the workload associated with voice-based in-vehicle interactions (e.g., cellular conversations or voice comands), where performance metrics, such as glancing patterns, are not directly impacted [10]. The heart activity records were identified as being sensitive to cognitive workload.…”
Section: Introductionmentioning
confidence: 98%
“…Reimer & Mehler [10] have demonstrated that physiological measures of workload can be productively modelled under simulated driving conditions. WMG's 3xD Desktop Driving Simulator for Intelligent Vehicles (Figure 1), consisting of Logitech G27 steering wheel, pedal set, gear lever, and three 22" screens, as well as, software developed by XPI Simulation Ltd., was used.…”
Section: B Desktop Simulator User Trialsmentioning
confidence: 99%
“…According to NHTSA [2], up to 94% of their observed accidents have occurred due to presence of human error that is, a car crash critical reason attributed to a driver. The cause of these errors is often an impaired mental and physical state of a driver, including fatigue [3], high level of workload [4], and distraction [5]. Similarly, presence of extensive emotions, especially anger, can make a driver prone to errors and could lead to dangerous driving [6].…”
Section: Introductionmentioning
confidence: 99%